2013
DOI: 10.1097/scs.0b013e31828a7ae5
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Dystopia Due to Orbital Roof Defect

Abstract: We performed a retrospective review of patients who presented with delayed dystopia as a consequence of an orbital roof defect due to fractures and nontraumatic causes to search for a correlation between orbital roof defect size and surgical indications for the treatment thereof. Retrospective analyses were performed in 7 patients, all of whom presented with delayed dystopia due to orbital roof defects, between January 2001 and June 2011. The causes of orbital roof defects were displaced orbital roof fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…16 Dysplasia of the greater wing of the sphenoid, as seen in 5% to 10% of cases of neurofibromatosis type 1, results in an ORD and can cause pulsatile proptosis from the transmission of cerebral pulsation. 17,18 Although generally considered congenital, it has been suggested that it can also develop or progress postnatally. 19 Congenital absence of a portion of the orbital roof with no associated syndrome or disease identified is a rare occurrence and has been reported to result in, or present with, vertical orbital dystopia.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…16 Dysplasia of the greater wing of the sphenoid, as seen in 5% to 10% of cases of neurofibromatosis type 1, results in an ORD and can cause pulsatile proptosis from the transmission of cerebral pulsation. 17,18 Although generally considered congenital, it has been suggested that it can also develop or progress postnatally. 19 Congenital absence of a portion of the orbital roof with no associated syndrome or disease identified is a rare occurrence and has been reported to result in, or present with, vertical orbital dystopia.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Rha et al 18 described a case series of 145 patients with ORF of which 47 (32.4%) had displaced fractures. Thirty-five of these (74.5%) were treated conservatively as they had no initial definite symptoms.…”
Section: When To Treatmentioning
confidence: 99%
See 3 more Smart Citations